2015
DOI: 10.1111/caim.12152
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Entrepreneurial Teams: The Give and Take of Trust and Conflict

Abstract: Entrepreneurship research lacks empirical evidence about interactions between entrepreneurial team members. This paper examines the role of trust (cognitive and affective) and conflict (task and relationship) on team performance (effectiveness and efficiency) of innovative entrepreneurial teams. Data originated from 88 incubator‐based entrepreneurial teams in Austria. Results indicate that cognitive trust is the cornerstone of innovative entrepreneurial team performance. To maximize efficiency, such teams woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 131 publications
(170 reference statements)
3
29
0
Order By: Relevance
“…Especially when examining psychological phenomena (such as personality and conflict processes), students can constitute an acceptable sample, as it can be assumed that these psychological phenomena are fundamental to all human beings, suggesting that the characteristics of and results from this sample would not differ markedly from a sample of the general population (see Welpe et al for comparable logic). Supporting this assumption, the average level of task conflict reported by the entrepreneurship students in this study, for example, is in line with levels of task conflict reported in real‐life teams in studies such as those of Ensley and Hmieleski () and Khan et al () (see Schenkel, Cornwall, and Matthews for a comparable approach of identifying similarities and differences between entrepreneurship students and a broader entrepreneurial population). This is one reason student samples have been used in other top‐tier entrepreneurship research, particularly that with a focus on psychological phenomena (e.g., Bönte, Procher, and Urbig ; Welpe et al ).…”
Section: Limitations and Directions For Future Researchsupporting
confidence: 87%
“…Especially when examining psychological phenomena (such as personality and conflict processes), students can constitute an acceptable sample, as it can be assumed that these psychological phenomena are fundamental to all human beings, suggesting that the characteristics of and results from this sample would not differ markedly from a sample of the general population (see Welpe et al for comparable logic). Supporting this assumption, the average level of task conflict reported by the entrepreneurship students in this study, for example, is in line with levels of task conflict reported in real‐life teams in studies such as those of Ensley and Hmieleski () and Khan et al () (see Schenkel, Cornwall, and Matthews for a comparable approach of identifying similarities and differences between entrepreneurship students and a broader entrepreneurial population). This is one reason student samples have been used in other top‐tier entrepreneurship research, particularly that with a focus on psychological phenomena (e.g., Bönte, Procher, and Urbig ; Welpe et al ).…”
Section: Limitations and Directions For Future Researchsupporting
confidence: 87%
“…Mixed: Varied greatly across the teams in my sample. Konradt, & Hertel (2006) 0.09 52 0.71 Gilson & Ammeter (2002) 0.48 34 Greer & Caruso (2007) 0.29 42 0.66 1.00 Hempel, Zhang, & Tjosvold (2009) 0.25 102 Hu (2012) 0.35 60 0.65 Joshi, Lazarova, & Liao (2009) 0.33 28 0.72 Kanawattanachai & Yoo (2007) 0.11 38 1.00 1.00 Khan, Breitenecker, Gustafsson, & Schwarz (2015) 0.61 88 1.00 1.00 Kirkman, Rosen, Tesluk, & Gibson (2006) 0.24 36 0.71 Lee, Gillespie, Mann, & Wearing (2010) 0.64 34 Mach & Lvina (2015b) 0.35 73 1.00 Mahoney, Korsgaard, & Pitariu (2012) 0.07 59 0.44 Moshier & Foti (2012) 0.10 36 0.60 Olson, Bao, Parayitam (2007) 0.40 252 Papenhausen (2006) 0.29 35 1.00 Parayitam & Dooley (2007) 0.65 109 Peterson & Behfar (2003) -0.10 67 0.66 Pitts (2010) 0.14 58 1.00 Rau (2005) -0.03 111 0.46 1.00 Rispens, Greer, & Jehn (2007) 0.76 27 0.71 0.62 Sanchez, Olson-Buchanan, Schmidtke, & Bradley (2009) 0.16 63 Small & Rentsch (2010) 0.28 60 0.59 1.00 Stewart & Gosain (2006) 0.10 67 1.00 Talaulicar, Grundei, & Werder (2005) 0.23 56 Webber (2008a) 0.74 31 20100.61 93 1.00 1.00 Groesbeck (2001) 0.71 100 0.69 Hempel, Zhang, & Tjosvold (2009) 0.19 102 Kanawattanachai & Yoo (2002) -0.02 36 1.00 1.00 Khan, Breitenecker, Gustafsson, & Schwarz (2015) 0.46 88 1.00 1.00 Lee, Gillespie, Mann, & Wearing (2010) 0.40 34 Mach & Lvina (2015b) 0.18 73 1.00 Olson, Bao, Parayitam (2007) 0.45 252 Parayitam & Dooley (2007) 0.15 109 Pitts (2010) -0.08 58 1.00…”
Section: Low Inference Codingmentioning
confidence: 99%
“…These help us to predict higher EO when the functional diversity of entrepreneurial team is high (Smart & Conant, 1994). Recent publications have reported that the role of diversity in an entrepreneurial team may have positive impacts on performance with the logic of entrepreneurial team diversity (Khan, Breitenecker, Gustafsson, & Schwarz, 2015;. Based on these ideas, the overall EO can be higher with higher functional diversity in entrepreneurial team.…”
Section: The Influence Of Functional Diversity In An Entrepreneurial mentioning
confidence: 96%
“…As the entrepreneurial outcomes are, more or less, attributable to the developed value by founders and team members' mutual expectations through entrepreneurial process, other scholars addressed the issue of cultural characteristics among team members such as shared value and trust (Khan, Breitenecker, Gustafsson, & Schwarz, 2015).…”
Section: Previous Research On Entrepreneurial Teammentioning
confidence: 99%